2007
DOI: 10.1016/j.seizure.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire study on knowledge of and attitudes toward epilepsy in schoolchildren and university students in Rome, Italy

Abstract: These findings suggest that apart from an encouragingly large number of the subjects we studied claim to know something about epilepsy (91% today versus 73% 22 years ago), Italian students still know little about epilepsy. These preliminary data should provide a starting point for a future in-depth population-based survey and information campaigns at schools in the Rome metropolitan area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 14 publications
5
32
2
1
Order By: Relevance
“…Moreover, it found a gender variation in attitudes as females had statistically significantly more positive attitudes than males [15]. Very limited knowledge about epilepsy was found in a study conducted among university and school students in Italy [16]. Similar limited knowledge was also reported for university students in Trinidad and Tobago [17].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, it found a gender variation in attitudes as females had statistically significantly more positive attitudes than males [15]. Very limited knowledge about epilepsy was found in a study conducted among university and school students in Italy [16]. Similar limited knowledge was also reported for university students in Trinidad and Tobago [17].…”
Section: Introductionsupporting
confidence: 52%
“…Although university graduates represent the most educated segment of modern societies, unfortunately, only few studies worldwide have assessed their knowledge about epilepsy and attitudes toward PWE [15][16][17][18][19][20]. For example, a study from Canada found that students' knowledge about epilepsy was variable but their attitudes were positive.…”
Section: Introductionmentioning
confidence: 99%
“…In our study we interviewed, 90 males & 180 females of a public sector medical college, in which 85.1% students consider epilepsy as a neurological disease as compared to a study performed on undergraduate medical students of Brazil, where 93.4% consider epilepsy as a brain disease [16], and an Indian study showed students who consider epilepsy as a neurological disease by 93.1% [11]. Although many students recognize brain disease as a cause of seizure, in an Italian study, 45% of the medical students perceived epilepsy as psychiatric illness, in a Malaysian study 39.7% of the undergraduate students regarded epilepsy as a mental illness, where as in our study this value is 3.7% [15].…”
Section: Discussionsupporting
confidence: 47%
“…Population based surveys show that knowledge of epilepsy is generally superior among people with higher socioeconomic status and better educated individuals (university and grad school students). It has also been evaluated through a variety of studies that, in comparison, health care students of various countries in the world (Brazil, India, Italy, Canada) have more knowledge of epilepsy [12,13,14,15,16]. In our study we interviewed, 90 males & 180 females of a public sector medical college, in which 85.1% students consider epilepsy as a neurological disease as compared to a study performed on undergraduate medical students of Brazil, where 93.4% consider epilepsy as a brain disease [16], and an Indian study showed students who consider epilepsy as a neurological disease by 93.1% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, dependendo da etiologia e do tipo de crise convulsiva, a Os resultados obtidos na presente amostra são corroborados pela literatura, uma vez que a maior parte das crianças apresentava dificuldades de aprendizagem, TDAH, além de problemas de comportamento o que acarretava em desajustes emocionais. No que tange aos problemas educacionais e dificuldades escolares estes podem estar associados às variáveis orgânicas da epilepsia, mas também ao desconhecimento sobre a doença por parte de colegas, professores, funcionários e outros membros do ambiente escolar (THACKER et al, 2008;AGUIAR et al, 2007;CHOMBA et al, 2007;MECARELLI et al, 2007;SHAFIQ et al, 2007;FERNANDES et al, 2007;AWAD;SARKHOO, 2007;DAOUD et al, 2007). Destes, 69% acreditavam que a epilepsia tem início no cérebro; para 28,7%, é uma aflição sobrenatural.…”
Section: Discussionunclassified